ANALISIS PERAN REGULATOR DAN ASPEK BIAYA DALAM PENCEGAHAN PRAKTIK PREDATORY PRICING DI E-COMMERCE INDONESIA - Dheny Biantara; Viona Margaretha; Iwan Lesmana (INDONESIAN JOURNAL OF ACCOUNTING AND GOVERNANCE, 2022)
This study analyzes the role of regulators and the cost aspects that can prevent predatory pricing in an E-Commerce. Cross-border sellers who are successful in offering lower prices pose a threat to local MSMEs. The government as the regulator decided to prohibit the import of 13 product categories in the E-Commerce marketplace to anticipate unhealthy business practices. This phenomenon is also known as predatory pricing. Predatory pricing is setting very low prices to beat competitors. The phenomenon that occurs from data taken from E-Commerce Shopee which focuses on competition between sellers where there are 13 products with "overseas" location filters are no longer found. The parameters used in this study are product similarity, selling price, and other information that can be used to support research analysis. The results of this study indicate that all categories experience marketing practices, although most categories are suspected of experiencing predatory pricing.